Two series of pH-dependent lanthanide complexes showing solvent-induced single crystal to single crystal transformation, sorption and luminescence properties1. Issue 14 (14th April 2015) - Zhang, Lina; Zhang, Chao; Zhang, Bin; Du, Chenxia; Hou, Hongwei
<x xml:space="preserve">Abstract</x> Two series of new lanthanide PCPs were produced under different pH values. Series B demonstrates fascinating solvent-induced dynamic behaviors in an SCSC manner.